Utilization Wisdom Local Coast as Context STEM-Based Science Learning in Junior High Schools throughout Tegal Regency - Ellianawati, Ellianawati; Subali, Bambang; Dwijananti, Pratiwi; Yulianti, Ian (Universitas Negeri Semarang, 2024)
Implementation The Independent Curriculum encourages teachers to plan learning that can direct participant educate For Study more broad and deep through environment surrounding areas . Teachers are required For Can develop device learning specifically teaching materials that can accommodate need Study participant educate . Based on results observations and interviews conducted , obtained data that science teachers in Tegal Regency still difficulty in compile teaching materials . This community service activity aims to provide structured training related to the development of teaching materials, integration of local wisdom, and the STEM approach to partners, namely the MGMP IPA Tegal Regency. The community service activity consistsof three stages, namely preparation, implementation, and evaluation. The results of the activity showed that the teachers were enthusiastic and provided positive feedback on the community service activities carried out. The teachers were helped by the training because it increased their knowledge related to local wisdom and the STEM approach, then gained direct experience in compiling teaching materials and LKPD.